Perceived Emotional Synchrony in Collective Gatherings: Validation of a Short Scale and Proposition of an Integrative Measure - Wlodarczyk, Anna; Zumeta, Larraitz; Pizarro, José Joaquin; Bouchat, Pierre; Hatibovic, Fuad; Basabe, Nekane; Rimé, Bernard (Frontiers in Psychology, 2020)
Over the past decade, there has been an increasing interest in the relationship between participation in collective gatherings and rituals, and different important psychosocial variables and processes, such as social sharing of emotions, group cohesion, identity fusion, prosocial tendencies and behaviours, and wellbeing (e.g., Khan et al., 2015b; Páez et al., 2015; Rimé, 2009; Xygalatas et al., 2013). These studies, coming from different lines of research, have proposed diverse explanatory mechanisms in order to explain the positive social and psychological effects of collective gatherings. In the present article, we focus on one of these mechanisms, known as collective effervescence, emotional communion, emotional entrainment or Perceived Emotional Synchrony (PES). First, we briefly discuss current conceptions of the emotional states and experience during collective gatherings and what they bring to the definition of PES. We close this point by proposing an integrative definition of PES. Second, structural validity of the original PES scale is examined. Third, incremental validity of PES is examined in two longitudinal studies, particularly with respect to wellbeing. Finally, a short form of PES Scale is exposed, integrating short scales that measures antecedents and behavioural effects of collective effervescence.